Russia's national image in Chinese social networks (based on the activity of RT's Weibo account) - Kong, Mengnan (Филология: научные исследования, 2025)
Official RT account in Weibo is considered from October 2019 to March 2025. With the development of mediatization of society, Russia pays special attention to the formation of its national image through international communications, using both domestic and foreign media to strengthen its influence in the world. In this context, RT has rapidly strengthened its position in the global media space, becoming a key tool for promoting the image of Russia and strengthening its international information agenda. At present, the comprehensive strategic partnership between Russia and China in the new era continues to deepen, and bilateral relations are experiencing the best period in their history. As a result, the image of Russia in Chinese social media has become significantly more positive and favorable compared with previous years. This paper collects and analyzes data from publications of the official RT Weibo account, including topics, countries, and positions covered in the news. Particular attention is paid to the ways of presenting issues related to Russian-Chinese relations and strategies for forming a national image. Quantitative analysis and content analysis are mainly used to summarize RT's communication activities on the Chinese social network Weibo. The image of Russia on Chinese social networks is becoming increasingly positive and popular, while RT purposefully increases the distribution of content dedicated to the strategic partnership between Russia and China; RT's agenda tends to align with China's official position, emphasize the idea of "multipolarity" and strengthen Russia's narrative of opposing Western hegemony; RT promotes the soft power of Russian culture through the popularization of literature, art, scientific and technological innovation, tourism and education, demonstrating to the Chinese audience the modern image of Russia as a great power. The study of data from the RT account on Weibo, in contrast to Western social networks such as Twitter and Facebook, allows us to study the strategies of Russian media adaptation to the Chinese censorship system and media environment; Including Russian-Chinese relations in an analytical framework to study how RT on Weibo creates common narratives and space for a unified position, shaping the image of a “partner country”.